The mechanisms mediating the antiepileptic effects of the ketogenic diet, and potential opportunities for improvement with metabolism-altering drugs. (November 2017) - Youngson, Neil A.; Morris, Margaret J.; Ballard, J. William O.
Abstract: The ketogenic diet (KD) is increasingly being used to treat patients with intractable epilepsy. Despite decades of research, the reason for its success, when anticonvulsants have failed, is still not completely understood. There are, however, many candidate mechanisms which can be grouped into those that alter neuronal excitability at the synapse, and those that confer neuroprotection. The molecular underpinning of these mechanisms centres on the shift from glucose- to lipid-based energy generation that accompanies a high fat/low carbohydrate diet. Here we describe how changes in the relative abundances of energy substrates (ketone bodies), intermediates of glycolysis and fat metabolism, and metabolic end products (ATP, reactive oxygen species) underlie many of the antiepileptic effects of the KD. We propose that the success of the KD for treating epilepsy lies in the large variety of antiepileptic mechanisms that it confers. Different subsets of the mechanisms may be clinically relevant in different patients. We extend this to suggest that the broad benefits of the KD could therefore be achieved by pharmacologically promoting the production of ketone bodies in the liver as they represent a key mediator that is common to all of the proposed mechanisms.